Fulminant Myocarditis Managed by Extracorporeal Life Support (Impella® CP): A Rare Case. (12th July 2017) - Fox, Henrik; Farr, Martin; Horstkotte, Dieter; Flottmann, Christian
Abstract : Background . Treating myocarditis can be difficult, as clear criteria for diagnosis and management are lacking for heterogeneous clinical presentations. Case Description . We report a case of a 49-year-old female who presented with cardiogenic shock and subsequent cardiac arrest. Extracorporeal life support was instituted, and after eight days with Impella CP the patient recovered and at six months presented with normal cardiac function. Conclusion . Fulminant myocarditis remains a challenging disease in daily clinical practice, not only for diagnosis, but also for treatment. With this report we emphasize that myocardial failure due to fulminant myocarditis may be reversible if treated with extracorporeal life support, which thus plays an important and life-saving role.